Co-Development of Education Aspirations and Postsecondary Enrollment Especially Among Students Who Are Low Income and Minority. Issue 2 (3rd April 2017) - Schneider, Barbara; Kim, Soobin; Klager, Christopher
Abstract : Most adolescents, regardless of their occupational aspirations, are educationally ambitious. However, these high education ambitions are often unaligned with their occupational ones. This misalignment between students' educational expectations and their desired careers can be personally and institutionally costly. In contrast to earlier studies of educational attainment and occupational status, which relied independently on educational expectations and occupational aspirations, this study views alignment as related and co-developing. Results show that educational expectations and occupational aspirations co-develop during high school. Misalignment between educational and occupational expectations is a significant determinant of eventual educational attainment and has implications for future labor market outcomes.